She lover of death : a Fandorin mystery - Akunin, B. (Boris) (Akunin, B. (Boris). Fandorin mystery., 2020)
"When Masha Mironova alights in Moscow at the turn of the century, with a modest inheritance and a determination to shed her provincial Siberian upbringing, she becomes Columbine: reckless and daring-and with the dramatic outfits to prove it. In her quest for danger and passion, Columbine soon discovers the Lovers of Death-a small gathering of poets who conduct seances to determine death's next chosen lover. Once named at a seance, the chosen one must await three signs from death before taking their own life. The resulting string of suicides has taken Moscow by storm, becoming fodder for sensational media coverage and widespread hysteria. As the group's numbers steadily dwindle, a mysterious newcomer appears. Immediately recognizable to the reader as the inimitable Fandorin, the newest member begins to sow doubt and discord from within, in order to ward Moscow's youth away from the lure of suicide and expose the sinister deception at the group's core. But will the gentleman detective be able to stop Columbine from taking action when she receives her three unmistakable signs? She Lover of Death is a fantastically entertaining murder mystery, where the murderer's weapons of choice are trickery and psychological manipulation"--